Damage Kinetics at the Sub-micrometric Scale in Bast Fibers Using Finite Element Simulation and High-Resolution X-Ray Micro-Tomography - Guessasma, Sofiane; Beaugrand, Johnny (Frontiers in Plant Science, 2019)
This study combines experimental testing and computation analysis to reveal the role of defects and sub-micrometric microstructure in tensile behaviour of hemp bast fibres. In particular, these structural defects represent the footprint of the processes to which the fibres elements are subject along the whole transformation chain from the plant to the end use product. Tensile experiments performed on elementary fibres and bundles in a wide diameter range (40 – 200 µm) are simultaneously conducted with X-ray micro-tomography observation. 3D images of ultra-fine resolution (voxel size of 280 nm) are achieved at different deformation magnitudes up to the complete failure thanks to the use of synchrotron radiation (ESRF, Grenoble, France). A Finite element model is implemented based on the conversion of the tomograms into 3D meshes. High performance computing is used to simulate the tensile response of the hemp bast fibres. In particular, the effects of notching and sub-micrometric structure of the fibres are explored. Results show the presence of different types of diffuse damage kinetics, which are related to the variability in the fibre size, surface defects and the presence of the lumen space. The damage behaviour is found to be sensitive to the type of stress criterion implemented in the finite element computation. The predictive analysis demonstrates the relevance of using embedded microstructure simulations to reveal the extent of stress localisation and predict the failure properties in bast fibres for innovative composite manufacturing for instance.